Safety evaluation of the food enzyme endo‐1,4‐β‐xylanase from the non‐genetically modified Trichoderma citrinoviride strain HBI‐TX01 - EFSA Panel on Food Enzymes (FEZ); Holger Zorn; José Manuel Barat Baviera; Claudia Bolognesi; Francesco Catania; Gabriele Gadermaier; Ralf Greiner; Baltasar Mayo; Alicja Mortensen; Yrjö Henrik Roos; Marize L. M. Solano; Monika Sramkova; et al. (EFSA Journal)
Abstract The food enzyme endo‐1,4‐β‐xylanase (4‐β‐d‐xylan xylanohydrolase; EC 3.2.1.8) is produced with Trichoderma citrinoviride strain HBI‐TX01 by HBI Enzymes Inc. The food enzyme is free from viable cells of the production organism. It is intended to be used in four food manufacturing processes. Since residual amounts of food enzyme–total organic solids (TOS) are removed in two food manufacturing processes, dietary exposure was calculated only for the remaining two processes. It was estimated to be up to 1.488 mg TOS/kg body weight (bw) per day in European populations. Genotoxicity tests did not indicate a safety concern. The systemic toxicity was assessed by means of a repeated dose 90‐day oral toxicity study in rats. The Panel identified a no observed adverse effect level of 1101 mg TOS/kg bw, the highest dose tested, which when compared with the estimated dietary exposure, resulted in a margin of exposure of at least 740. A search for homology of the amino acid sequence of the food enzyme to known allergens was made and no match was found. Known sources of food allergens were used in the manufacturing process. The Panel considered that the risk of allergic reactions upon dietary exposure to this food enzyme cannot be excluded, but the likelihood is low. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns, under the intended conditions of use.